The Australian community methicillin resistant Staphylococcus aureus endemic : clonal spread or multiple evolutionary events - Coombs, Geoffrey Wallace (Curtin University, 2012)
Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) was first reported in remote indigenous communities living in the sparsely populated Kimberley region of Western Australia (WA). Between 1989 and 1995 five Panton Valentine leucocidin (PVL) negative clones were isolated from these communities: ST1-MRSA-IVa [2B] (WA-MRSA-1), ST78-MRSA-IVa [2B] (WA-MRSA-2), ST5- MRSA-IVa [2B] (WA-MRSA-3), ST45-MRSA-V [5C2] (WA-MRSA-4), and ST8- MRSA-IVa [2B] (WA-MRSA-5).Between 1995 and 2003, S. aureus screening of the indigenous populations living in 11 of these remote communities showed the S. aureus population consisted of 13 multilocus sequence type clonal complexes (CCs) and two Singleton lineages. Although five lineages contained MRSA, the MRSA lineages were not the predominant methicillin-susceptible S. aureus (MSSA) lineages. There was greater diversity amongst the MSSA, while the MRSA appeared to have emerged clonally following acquisition of the staphylococcal cassette chromosome mec (SCCmec) element. The emergence of CA-MRSA clones in different CCs indicates horizontal transmission of the SCCmec element into S. aureus had occurred on at least six occasions: SCCmec IVa [2B] into CC1 (ST1), CC5 (ST5), CC8 (ST8), CC45 (ST45), CC88 (ST78) and SCCmec V [5C2] into CC45 (ST45). Based upon the spa type and the DNA microarray profile six evolutionary events have subsequently occurred on at least three occasions from these clones (i.e. vertical transmission of the SCCmec element): twice from WA-MRSA-1, WA-MRSA-3, and WA-MRSA-5. Vertical transmission of the SCCmec element has not been identified for WA-MRSA-4 or WA-MRSA-2. The most prevalent MSSA lineage in the communities was the PVLpositive Singleton ST93 clone. As ST93-MRSA-IVa [2B], colloquially known as Queensland CA-MRSA, has become the most prevalent CA-MRSA in Australia, it was surprising in an environment of high β-lactam use and frequent horizontal transmission of SCCmec IVa a methicillin-resistant variant of ST93-MSSA was not found.Within these indigenous communities people colonised with MSSA tended to harbour clones of a different genetic lineage at each anatomical site while people colonised with MRSA tended to harbour clones of the same lineage at each site. Although the anterior nares is the preferred screening site for population studies, in this study many isolates of S. aureus would have been missed if throat and skin lesions had not also been swabbed. Three MRSA clones (WA-MRSA-1, WAMRSA- 2, and WA-MRSA-3) considered to be endemic in these communities have subsequently become predominant clones in the wider Australian community.Although WA-MRSA-1, WA-MRSA-2, WA-MRSA-3 and Queensland CA-MRSA predominate, the CA-MRSA population in Australia is genetically diverse. In WA, between 2003 and 2010, 83 unique pulsed-field gel electrophoresis (PFGE) strains were described from which 46 multilocus sequence types have been characterised. Forty five of these sequence types (STs) were from 18 CCs and two Singletons. While SCCmec IV and V were the predominant SCCmec elements, SCCmec VIII and several novel and composite SCCmec elements were present. The emergence of MRSA in diverse S. aureus CCs suggest horizontal transmission of the SCCmec elements has occurred on multiple occasions. Furthermore, DNA microarray and spa typing suggest horizontal transfer of SCCmec elements has also occurred within the same CC. For many single and double locus variant CA-MRSA clones only a few isolates were detected. This suggests the successful evolution of a CA-MRSA clone may not only depend on the mobility of the SCCmec element but also on other genetic determinants.As WA CA-MRSA, colloquially known as “WA-MRSA” are typically PVL negative many of the MRSA infections in WA have been superficial skin infections. However with the recent introduction of PVL-positive CA-MRSA more severe skin and soft tissues infections accompanied with a significant decrease in the age of patients have been observed.In 2010, 22% of CA-MRSA isolated in WA were PVL positive, with Queensland CA-MRSA being the predominant PVL-positive clone. The emergence of Queensland CA-MRSA (ST93-MRSA-IVa [2B]) has been due to independent acquisitions of different dru-defined type IV and type V SCCmec elements in several spa-defined ST93-MSSA backgrounds. Rearrangement of the spa sequence in ST93-MRSA has subsequently occurred in some of these strains. Although multiple ST93-MRSA strains were identified, PVL-positive ST93-MRSA-IVa [2B]-t202-dt10 was the predominant strain. Whether this strain arose from one PVL-positive ST93- MSSA-t202 or by independent acquisition of SCCmec-IVa [2B]-dt10 into multiple PVL-positive ST93-MSSA-t202 strains is yet to be determined.Several international PVL-positive clones have been introduced into WA, including the CC59 strain ST59-MRSA-VT [5C2&5] (Taiwan CA-MRSA clone), and the CC8 strain ST8-MRSA-IV [2B] (USA300). Genetic analysis of these strains indicated they are distinct from WA CA-MRSA clones.Although ST59-MRSA-VT [5C2&5] (Taiwan CA-MRSA clone) was found to be the most prevalent CC59 clone isolated in WA, independent evolution of PVL-negative CC59 CA-MRSA has occurred. Using a variety of molecular techniques, six distinct groups of CC59 were differentiated. Within these groups at least seven different variants of SCCmec elements were distinguished; (IVa [2B], IVb [2B], IVd [2B], IVa [2B]&5, IVv [2B], Vv [5C2], and V [5C2&5]. This suggests rapid evolution and/or multiple transfer events of SCCmec have occurred within this CC. Although some CC59 isolates in WA have overseas origins (eg Taiwan CA-MRSA clone and possibly USA1000), PVL-negative CC59 lineages unique to WA have acquired various SCCmec types on multiple occasions.The PVL-positive ST8-MRSA-IV [2B] strain isolated in WA was found to be closely related to USA300, with most isolates unable to be distinguished from USA300- TC1516. Some isolates however varied in their carriage of resistance and virulence determinants and therefore USA300 in Australia cannot be regarded as being genetically homogeneous. Altogether 16 variants were identified. Notably some isolates did not harbour the ACME locus, which is intriguing because this locus is assumed to be involved in facilitating the spread of USA300 by skin contact.In conclusion, this thesis has shown “WA-MRSA” arose in remote indigeneous communities located in WA, and three of these clones have subsequently become the most prevalent MRSA clones in Australia. However “WA-MRSA” did not arise from the predominant MSSA clones isolated from these remote communities. Although the vertical and horizontal transmission of SCCmec elements into S. aureus has occurred on multiple occasions in the WA community only three “WA-MRSA” clones have found an ecological niche. These three PVL negative clones harbour few additional resistance and virulence genes which paradoxically may contribute to their success. PVL-positive CA-MRSA infections have become more prevalent in young Australians. Although primarily due to Queensland CA-MRSA, international PVL-positive CA-MRSA clones are present in Australia.